An Investigation on the Effect of Endwall Movement on the Tip Clearance Loss Using Annular Turbine Cascade - Hesham M. El-Batsh; Magdy Bassily Hanna (International Journal of Rotating Machinery)
The aerodynamic losses in gas turbines are mainly caused by profile loss secondary flow, and tip leakage loss. This study focuses on tip leakage flow of high-pressure turbine stages. An annular turbine cascade was constructed with fixed blades on the casing, and the distance between blade tip and the hub was considered as tip clearance gap. The effect of endwall movement on loss mechanism was investigated by using experimental and numerical techniques. The measurements were obtained while the hub was fixed but the numerical calculations were carried out for both stationary and moving cascades. Upstream and downstream flows were measured by using a calibrated five-hole pressure probe. The steady incompressible turbulent flow was obtained by solving Reynolds averaged Navier-Stokes equations and by employing shear stress transport (SST) k-ω turbulence model. The total pressure loss coefficient obtained from the numerical technique was compared with the experimental measurements, and the comparison showed good agreement. Tip clearance vortices were observed in the tip clearance gap. It was found through this study that end-wall movement reduces tip leakage loss through the cascade.